Effective risk governance for environmental policy making: a knowledge management perspective - Mauelshagen, Craig William; Smith, Mark; Schiller, Frank; Denyer, David; Rocks, Sophie A.; Pollard, Simon J. T. (Elsevier, 2014)
Effective risk management within environmental policy making requires knowledge on natural, economic and social systems to be integrated; knowledge characterised by complexity, uncertainty and ambiguity. We describe a case study in a (UK) central government department exploring how risk governance supports and hinders this challenging integration of knowledge. Forty-five semi-structured interviews were completed over a two year period. We found that lateral knowledge transfer between teams working on different policy areas was widely viewed as a key source of knowledge. However, the process of lateral knowledge transfer was predominantly informal and unsupported by risk governance structures. We argue this made decision quality vulnerable to a loss of knowledge through staff turnover, and time and resource pressures. Our conclusion is that the predominant form of risk governance framework, with its focus on centralised decision-making and vertical knowledge transfer is insufficient to support risk-based, environmental policy making. We discuss how risk governance can better support environmental policy makers through systematic knowledge management practices.
Keywords: Environmental policy; Risk; Enterprise risk management; Knowledge management